PROSES PENGEMBANGAN KECERDASAN SOSIAL ANAK USIA DINI MELALUI DRAMA: Penelitian Tindakan terhadap Siswa-siswa Taman Kanak-kanak Laboratorium Percontohan Universitas Pendidikan Indonesia Kelas Nol Besar. - Sukanta, - (2010)
This study is titled "The Social Intelligence Development Process of Early Childhood by Drama" (An Action Research toward Kindergarten Student of Laboratorium Percontohan UPI). The social intelligence involves social awareness (experiences other feeling) and social facility (what to be done with the feeling). The point of social intelligence is empathy that expressed by attitude and behavior of feeling , understanding, and acting fit with other people expectation. Empathy requirement consists of emotional language mastery, sensitivity to other people feeling, and being harmonious with other people feeling in social interaction context. Those component of empathy need to be practiced to our children since their early childhood. The most effective way to re for realize that practice is through drama. The research method used is action research with drama treatment. Subject of this research are 43 students of Laboratorium percontohan UPI at Jl. Dr. Setiabudhi No. 229 Bandung. Data collection technique used is direct observation. Involved in children plays situation that led to production processes of drama. At the same time, researcher carry out unstructured interview with the subject of the research to gain the particular data categories. At the end of drama production processes, children perform their language capability, sensitivity, and action in front of the audience By the above facts, the researcher concluded that the process of drama is the process of having feeling of empathy. Because with this, process of values actualization initiated by the actors/actress will be performed in front of audience and responded by empathetically. By having drama activities, children experience habitual processes of practicing their emotional language and their sensitivity which integrated in the form of acting. There are two big activities in drama, i.e. interpretation and presentation (performance). Interpretation process occurred in three ways (triangle of empathy) involving the interpretation of author through his/her script, director concept, and characters of the story. The presentation is the product of interpretation process to be communicated in front of audience. The presentation is also a result of transformation process of actual living values that become symbolical drama performance living values.